Hadith #2174 - Sunan Abi Dawud - Abdullah bin 'Isa bin 'Abdur Rahman عبد الله بن عيسى بن عبد الرحمن; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ammar bin Razayq عمار بن رزيق; Ikrama عكرمة; Yahya bin Y'amar يحيى بن يعمر; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
AbuNadrah reported: An old man of Tufawah said to me: I was a guest of AbuHurayrah at Medina. I did not find any one of the companions of the Prophet (ﷺ) more devoted to worship and more hospitable than AbuHurayrah. One day I was with him when he was sitting on his bed. He had a purse which contained pebbles or kernels. A black slave-girl of his was sitting below. Counting them he was glorifying Allah. When the pebbles or the kernels in the purse were finished, she gathered them and put them a
Grade: Da'if

Hadith #2912 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; Amr bin Abi Hkym عمرو بن أبي حكيم الواسطي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: Islam increases and does not diminish. He, therefore, appointed a Muslim heir (of a non-Muslim).
Grade: Da'if

Hadith #4175 - Sunan Abi Dawud - Ammar ibn Yasir; Ata' bin Abi Muslim عطاء بن أبي مسلم; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
The Prophet (ﷺ) said: If a woman fumigates herself with perfume, she must not attend the night prayer with us. Ibn Nufayl said: Isha’ means night prayer.
Grade: Sahih

Hadith #4176 - Sunan Abi Dawud - Ammar ibn Yasir; Ibn Jurayj ابن جريج; Muhammad bin Bakr bin 'Uthman al-Barsani محمد بن بكر بن عثمان البرساني; Nasr bin 'Ali bin Nasr bin 'Ali; Umar bin 'Ata'a bin Abi al-Khawar عمر بن عطاء بن أبي الخوار; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
I came to my family at night (after a journey) with my hands chapped and they perfumed me with saffron. In the morning I went to the Prophet (ﷺ) and gave him a greeting, but he did not respond to me nor did he welcome me. He said: Go away and wash this off yourself. I then went away and washed it off me. I came to him but there remained a spot of it on me. I give him a greeting, but he did not respond to me nor did he welcome me. He said: Go away and wash it off yourself. I then went away and
Grade: Hasan

Hadith #4599 - Sunan Abi Dawud - Ammar ibn Yasir; Ata' bin Abi Muslim عطاء بن أبي مسلم; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
The Prophet (ﷺ) said: The best of the actions is to love for the sake of Allah and to hate for the sake of Allah.
Grade: Da'if

Hadith #4693 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Kahmas bin al-Hasan al-Tamimi كهمس بن الحسن التميمي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
Allah created Adam from a handful which he took from the whole of the earth ; so the children of Adam are in accordance with the earth : some red, some white, some black, some a mixture, also smooth and rough, bad and good.
Grade: Sahih

Hadith #4694 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Uthman bin Ghyath عثمان بن غياث; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
We attended a funeral at Baql’ al-Gharqad which was also attended by the Messenger of Allah (May peace be upon him). The Messenger of Allah (May peace be upon him) came and sat down. He had a stick (in his hand) by which he began to scratch up the ground. He then raised his head and said : The place which every one of you and every soul of you will occupy in Hell or in Paradise has been recorded, and destined wicked or blesses. A man from among the people asked : Prophet of Allah! Should we no
Grade: Sahih

Hadith #5168 - Sunan Abi Dawud - Abdullah bin 'Isa bin 'Abdur Rahman عبد الله بن عيسى بن عبد الرحمن; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ammar bin Razayq عمار بن رزيق; Ikrama عكرمة; Yahya bin Y'amar يحيى بن يعمر; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
I came to Ibn ‘Umar when he set his slave free. He took a stick or something else from the earth and said; for me there is no reward even equivalent to this. I heard the Messenger of Allah (May peace be upon him) say: If anyone slaps or beats his slave the atonement due from him is to set him free.
Grade: Sahih

Hadith #5241 - Sunan Abi Dawud - Aabad bin 'Aabad bin Habib عباد بن عباد بن حبيب بن المهلب; Abu Dharr al-Ghaffari; Ahmed bin Manay' أحمد بن منيع; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yahya bin Aqyl يحيى بن عقيل; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
I asked Hisham ibn Urwah about the cutting of a lote-tree when he was leaning against the house of Urwah. He said: Do you not see these doors and leaves? These were made of the lote-tree of Urwah which Urwah used to cut from his hand? He said: There is no harm in it. Humayd’s version adds: You have brought an innovation, O Iraqi! He said: The innovation is from you. I heard someone say at Mecca: The Messenger of Allah (ﷺ) cursed him who cuts a lote-tree. He then mentioned the rest of the tra
Grade: Hasan

Hadith #5242 - Sunan Abi Dawud - Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; Abu Dharr al-Ghaffari; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان; Yahya bin Aqyl يحيى بن عقيل; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: A human being has three hundred and sixty joints for each of which he must give alms. The people asked him: Who is capable of doing this ? He replied: It may be mucus in the mosque which you bury, and something which you remove from the road; but if you do not find such, two rak’ahs in the forenoon will be sufficient for you.
Grade: Sahih